Knowledge and Innovation in the Indonesian Artisanal Furniture Industry - Marina van Geenhuizen; Nurul Indarti (European Regional Science Association (ERSA), 2006)
In developed countries, localized learning in clusters of small and medium-sized firms is seen as beneficial for innovation in these firms. This paper questions whether such a situation is also true for small firms in developing countries. By examining 90 furniture manufacturers in the district of Jepara (Indonesia) we observe knowledge access mainly through one-sided local learning mechanisms, e.g. in-house learning-by-doing and informal contacts with buyers (contractors). This pattern tends to cause a dominance of product innovation (changes in design) and low levels of newness, and points to a lack of advantages from local learning. The major principle behind this is the way in which subcontracting relations are structured. However, the furniture manufacturers in Jepara are willing to connect with global knowledge, but financial obstacles prevent a change. This situation calls for the establishment of centres or renewal of existing centres where global knowledge can be accessed e.g. through the Internet, and support can be given in absorption of the new knowledge.
Keywords: 330